FENOMENA “MENDADAK ATLET” - Jahrir, Andi Sahrul; Oruh, Shermina; Agustang, Andi (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
The “Sudden Athlete” phenomenon reflects a sudden change in people's participation in sporting activities. The two main factors that influence this phenomenon are internal and external factors. Internal factors involve efforts to maintain fitness, changing lifestyle, releasing stress, and personal achievement through exercise. Meanwhile, external factors include physical conditions and medical recommendations, social trends, and inspiration from other people. The impact of this phenomenon involves the formation of sports communities, sportainment concepts that combine sports and entertainment, the growth of the sports industry, and the development of sports tourism. The writing method used in this research uses literary studies, this article presents a comprehensive overview of the aspects related to the